Understanding the evolving state of deforming polycrystals using synchrotron x-rays. (August 2019) - Miller, Matt; Budrow, Chris; Long, Tim; Obstalecki, Mark
Abstract: The multiscale nature of irreversible processes like plasticity make them particularly challenging. One must be looking everywhere, all the time to gain a predictive understanding of plasticity–related processes such as fatigue crack initiation. High energy (HE) synchrotron x-ray diffraction is a unique tool for characterizing the state of an entire aggregate of metallic crystals with sub-crystal resolution. Combined with in situ loading, HE x-ray diffraction provides experimental hope for characterizing the conditions leading to the initiation of a crack. In this work, we conducted a HE x-ray diffraction experiment on a commercially pure copper sample subjected to in situ cyclic loading at the F2 Station at the Cornell High Energy Synchrotron Source (CHESS). We observed that the evolution of lattice orientation distributions within each crystal evolved as the specimen was loaded through complete fatigue cycles. We defined a "size" of these orientation clouds, which we called Θ ¯ . Changes in Θ ¯ are related to the plasticity-induced state of each crystal. We saw significant evolution of the Θ ¯ distributions as the sample went through cycle 2. By cycle 256, the evolution of the Θ ¯ distribution was significantly reduced - consistent with the saturation of cyclic hardening that we see on the macroscale. We also saw that the 40 crystals with the largest values of Θ ¯ in the first half cycle had a larger amount of Θ ¯ accumulation on average over the 256 cycles than the rest of the crystals in the aggregate.